Crisis and memory: Exploring social aspects of the economic recession in the scientific literature and oral narratives - Souyioultzoglou, Irakleitos; Angelaki, Marina (The Greek Review of Social Research, 2021)
The article proposes a broader understanding of crises as primarily social phenomena and focuses on the discursive dynamics of the Greek crisis. The methodological approach lies in the comparative analysis of the discourses about the “crisis” as an analytic category and social phenomenon, focusing on the convergent and/or divergent experiences of informants and the related literature regarding the different social/economic aspects of the crisis. To analyze the discourses generated by the Greek crisis, we examine the literature that focuses on the multifaceted impact of the crisis on daily activities, while in parallel we also benefit from the interviews conducted by the Oral History Groups to understand how the discourse about the crisis is shaped by the inherent characteristics of the Greek society and the social awareness of its members.